Inter-rater reliability of the AFTD-pitting test among elderly patients in a long-term medical facility - Dai, Misako; Sugama, Junko; Tsuchiya, Sayumi; Sato, Aya; Matsumoto, Masaru; Iuchi, Terumi; Maeba, Hiroko; Okuwa, Mayumi; Sanada, Hiromi; Moffatt, Christine J. (International Lymphoedema Framework Japan, 2015)
BACKGROUND and AIM: The pitting test has been reported in various methods as a standard for evaluating chronic oedema, but a unified method has not been determined. This makes it difficult to accurately specify the prevalence of oedema. The present study aimed to evaluate inter-rater reliability of the AFTD-pitting test, which included 4 factors: Anatomical locations of oedema; Force required to pit; the amount of Time; and the Definition of oedema. The present study is the first stage of an international epidemiological study of chronic oedema. METHODS: This cross-sectional observational study was performed at a long-term care hospital in Ishikawa Prefecture, Japan. The inter-rater reliability of the pitting test for evaluating oedema using the AFTD-pitting test was tested for 34 locations on the body, with 10 seconds of pitting with a similar force to that of the reference rater and assessed using the modified Fukazawa method. One reference rater and four raters evaluated oedema in five patients. Then, the agreement rate and Cohen-s kappa coefficient were calculated. RESULTS: All protocols were completed by four raters for five bedridden patients. Agreement among the four raters was high, at >0.85, and the kappa coefficient showed almost perfect, moderate, and fair agreement for one (0.81), four (0.51-0.60) rater, respectively. CONCLUSION: The inter-rater reliability of four nurses who applied the AFTD-pitting test was high, and the kappa coefficient showed at least fair agreement. Therefore, the AFTD-pitting test is a useful method to assess whole-body chronic oedema.